UJI ANTIBAKTERI EKSTRAK JAHE MERAH Zingiber officinale var. Rubrum TERHADAP Staphylococcus aureus DAN Escherichia coli - Handrianto, Prasetyo (2477 - 6165, 2016)
The study of inhibition testing antibacterial extract Fresh Red Ginger Zingiber officinale var. Rubrum Against Staphylococcus aureus, and Escherichia coliguna to determine the source of antibacterial natural products, especially red ginger has been conducted. Anti-bacterial inhibition test using disc diffusion method with fresh red ginger rhizome material. The study was conducted using concentrations: 0%, 20%, 40%, 60%, 80%, and 100%. Concentration of 0% was used as a negative control. The data obtained will be tested statistically using ANOVA with sig. 0.05. The results showed that the extraction of fresh red ginger (Zingiber officinale var. Rubrum) at a concentration of 100% has the highest inhibitory region to S. aureus (15.83 mm)and E. coli (14:22 mm). It can be concluded that the extract of fresh red ginger Zingiber officinale var. Rubrum at a concentration of 100% has a moderate level of inhibition to S. aureus and weak level of inhibition to E. coli. Keywords: Escherichia coli, Fresh red ginger extract of Zingiber officinale var. Rubrum, Staphylococcus aureus.